Outlook in life of older adults and their health and community condition. Issue 10 (2nd October 2020) - Ramos, Mary Dioise; Brown, Austin
ABSTRACT: Positive outlook in life is believed to help safeguard aging people against the negative experiences and considered to reduce the risk of health diseases. We analyzed the health condition, cognition, mobility, and community condition of 4, 692 older adults from the National Health and Aging Trends Study based on their outlook in life: positive, negative, and neutral group. The presence of heart disease, high blood pressure, arthritis, and lung disease contributes to older adults' negative outlook in life. Most older adults who belong to the positive outlook group rated their memory as very good. In contrast, most older adults in a negative outlook group perceived their memory as fair and poor, and mostly need the help of others to leave the house and have trust issues. The findings may provide new opportunities by intervening with policies and practices that generally may intensify a positive outlook in life.